GAMBARAN KEJADIAN MALARIA DI KABUPATEN ACEH BARAT SETELAH STATUS ELIMINASI TAHUN 2018 - Dwi Haryatmi; Wuryawan Wuryawan (LPPM Universitas Abdurrab, 2026)
After achieving malaria elimination status in 2018, West Aceh Regency faced challenges in the form of imported malaria cases and the emergence of zoonotic cases due to interactions with forests. This descriptive study with a secondary data analysis design (Retrospective Cohort Study) aims to analyze temporal trends, demographic characteristics (people), regional distribution (places), and types of malaria parasites for the period 2019–2025. Total sampling was conducted on all malaria cases at the West Aceh Regency Health Office with an accumulation of 61 cases, where trend analysis was calculated using simple linear regression. The results showed that all samples were positive for malaria where there was a temporal spike in 2025 of 19 cases. Infection cases were absolutely dominated by men (98.2%), all of whom were in the productive age group (100%), worked in the military sector (80.32%), were forest encroachers, or illegal gold miners, with the majority being imported cases (96.72%). From the characteristics of the parasite, the threat of an etiological shift from human malaria (P. falciparum and P. vivax) to zoonotic malaria of long-tailed macaques, Plasmodium knowlesi, was found. In conclusion, the macro-elimination status of the region remains maintained with an Annual Parasite Incidence (API) value of <1 per 1,000 population (API = 0.087) but there is a vulnerability to post-elimination malaria in West Aceh triggered by occupational risks, high geographic mobility of productive-age men, and the threat of hidden transmission of P. knowlesi zoonosis due to the impact of forest deforestation